Strength Analysis of the Frame Structure with the Impact Load Between the ASTM A36 And JIS G3101 Materials in the Electric Car E-Falco - Hadi Pranoto; Bambang Darmono; Gama Widyaputra (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2022)
Designing a vehicle frame, selecting materials and determining the factors of safety and comfort are a very important thing very important. So that the safety of the driver is a concern important when the car has an accident. Research methods used is a simulation using the method finite element. Impact testing modeling mechanism that done is full-width frontal impact. This crash test variation was carried out on the frame structure of the E – Falco electric car. The research compares the two materials to be applied to the frame namely ASTM A36 and JIS G3101 materials. Variation of speed applied to the impact testing of this research is 40 km/hour, 60 km/hour, and 100 km/hour. After the analysis process is carried out, obtained the maximum deformation of the frame on the ASTM A36 material with a speed of 100 km/h is 176.57 mm and at JIS G3101 material is 175.09 mm. The maximum stress value obtained in a frame with ASTM A36 material with a speed of 100 km/hour is 4488 MPa and the JIS material G3101 is 4475 MPa. The maximum strain value obtained frame with ASTM A36 material with a speed of 100 km/hour is 2.46E-02 and the JIS G3101 material is 2.52E-02. The frame with ASTM A36 material has a safety factor of 2.4 and the JIS material G3101 has a safety factor of 3.1.